Patient-reported quality-of-life and sexual-function outcomes after laparoscopic supracervical hysterectomy (LSH) versus total laparoscopic hysterectomy (TLH): a prospective, questionnaire-based follow-up study in 915 patients - Brucker, Sara; Sohn, Christof; Wallwiener, Markus (Archives of gynecology and obstetrics, 2014)
Purpose: To compare patient-reported quality-of-life and sexual function outcomes in women after laparoscopic supracervical hysterectomy (LSH) or total laparoscopic hysterectomy (TLH) for benign uterine disease. Methods: Out of a cohort of 1,952 patients from a previous implementation study of LSH and TLH, 1,886 patients who had not undergone intraoperative conversion to laparotomy or were ineligible for other reasons were invited by mail to participate in this prospective, questionnaire-based follow-up study. Results: Of the 915/1,952 (48.5 %) survey respondents included in the analysis, 788 (86.1 %) and 127 (13.9 %) had undergone LSH or TLH, respectively. Women undergoing LSH reported significantly lower pain levels (p = 0.037) and faster partial (p = 0.015) and complete (p < 0.001) resumption of normal daily activities compared to those undergoing TLH. As regards sexual function, women undergoing LSH resumed sexual activity significantly sooner (p = 0.018), rated sexual desire as higher (p = 0.023), and reported more frequently that their sexual life had improved postoperatively (p = 0.008) than did women undergoing TLH. Conclusions: Women undergoing LSH for benign uterine disease may have better outcomes regarding certain quality-of-life and sexual function parameters than women undergoing TLH for benign uterine disease.
Gesehen am 16.10.2020